Leviticus : a book of ritual and ethics - Milgrom, Jacob, 1923-2010 (Continental commentaries., 2004)
Building upon his life-long work on the Book of Leviticus, Milgrom makes this book accessible to all readers. He demonstrates the logic of Israel's sacrificial system, the ethical dimensions of ancient worship, and the priestly forms of ritual.